The role of village institutions based on open government partnerships in nature conservation: a case study in a village in Indonesia - Nursetiawan, Irfan; Wardani, Ari Kusumah; Distrito, Caesar (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2023)
This study aims to analyze the role of village institutions in an effort to preserve nature in Sukamaju Village, Cihaurbeuti District, Ciamis Regency, as nature conservation has become an increasingly important issue in the context of sustainable development at this time. Village institutions have the potential to play a role in maintaining natural sustainability and promoting a balance between the use of natural resources and the needs of rural communities. The study employed a qualitative research method by means of data collection in the form of in-depth interviews, observation, and document study. The study resulted in the finding that village institutions in Sukamaju Village play a significant role in nature conservation. Several institutional forms are involved, such as farmer groups, youth organizations, community information groups, forest village community institutions, and tourism awareness groups. The roles of village institutions include managing natural resources in a sustainable manner, monitoring activities that damage the environment, educating and socializing the importance of nature conservation to the community, as well as developing programs and activities that support natural sustainability. This study also identified several challenges faced by village institutions in carrying out their roles. These challenges include limited human resources, limited funds, conflicts of interest between the use of natural resources and the economic needs of the community, as well as the lack of awareness and participation of the community in nature conservation. In this context, this study provides recommendations for strengthening the role of village institutions in nature conservation, including by increasing institutional capacity, supporting the development of sustainable environment-based economic activities, increasing community participation, and building cooperation with related parties such as local governments, research institutions, and non-governmental organizations. In addition, the Sukamaju Village Government is expected to be able to initiate climate village-based programs.